Environmental and management impacts in turfgrass systems: nitrous oxide emissions, carbon sequestration, and drought and traffic stress - Braun, Ross Charles (Kansas State University, 2017)
Turfgrasses sequester and emit carbon dioxide, and emit nitrous oxide (N₂O) when fertilized with nitrogen and irrigated. Future water availability is a serious issue and drought restrictions may be imposed on turf managers while turf areas are subjected to traffic stress. My objectives in Chapter 2 were to: 1) quantify the magnitude and patterns of N₂O emissions and carbon (C) sequestration in zoysiagrass (Zoysia japonica Steud.); and 2) determine how irrigation (66% and 33% reference evapotranspiration [ET₀] replacement) and fertilization (polymer-coated urea, urea, and unfertilized) management may reduce N₂O emissions and enhance carbon sequestration. My objectives in Chapters 3 and 4 were to evaluate above- and below-ground responses of cool-season (C3) [Kentucky bluegrass (Poa pratensis L.) and perennial ryegrass (Lolium perenne L.)] and warm-season (C4) grasses {buffalograss [Buchloe dactyloides (Nutt.) Engelm] and zoysiagrass] at golf course-related mowing heights [1.6-cm (fairway) and 6.4-cm (rough)], with and without traffic during a simulated drought and subsequent recovery period (without traffic). In Chapter 2, N₂O emissions increased by 6.3% with more irrigation during summers and increased from 4.06 kg ha⁻¹ in unfertilized turf to 4.50, and 5.62 kg ha⁻¹ in polymer-coated urea and urea treated turf, respectively, during the 2-year study. There was no difference in C sequestration rates between a high vs. low input management schedule. The C sequestration rate was 0.952 Mg C ha⁻¹ yr⁻¹ for zoysiagrass when averaged across management schedules and depths. The use of a controlled-release fertilizer such as PCU compared to the use of a quick-release fertilizer and/or lower irrigation will reduce N₂O emissions in turfgrass. In Chapters 3 and 4, the better drought tolerance of C4 grasses led to more differences between traffic treatments within C4 than C3 grasses, but C4 grasses maintained the highest quality and green cover. Quality at rough- compared to fairway-height was more impacted by traffic. Decreasing soil moisture due to drought led to a minimal impact from traffic on soil bulk density, soil penetration resistance (SPR), and root measurements. During drought, SPR at deeper soil depths and fairway plots increased and exceeded the critical value of 2.0 MPa. Both C4 grasses and perennial ryegrass had larger root diameters, which may have led to better soil compaction resistance. Traffic during drought will have a negative and accelerated impacts above-ground, but minimal impact below-ground, which will vary with turf species and mowing height.
Keywords: Fertilization; Controlled-release fertilizer; Water conservation; Deficit irrigation; Golf courseGreenhouse gases